Method for preparing ammonia material TiOx / MIL-101 (Cr)-NO2 through photocatalytic nitrate reduction
By using atomic layer deposition technology to deposit TiOx in MIL-101(Cr)-NO2, the TiOx/MIL-101(Cr)-NO2 composite material is formed, which solves the problems of high energy consumption and environmental pollution in the Haber-Bosch process, and achieves a low-energy and efficient photocatalytic ammonia reduction effect.
Patent Information
- Application Number
- CN202510019810.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
AI Technical Summary
The existing ammonia preparation method mainly relies on the Haber-Bosch process, requiring high temperature and high pressure, resulting in high energy consumption and environmental pollution. At the same time, the accumulation of nitrates in fertilizer runoff and industrial wastewater poses a threat to the environment and human health.
Atomic layer deposition technology is used to deposit TiOx in the confined domain of MIL-101(Cr)-NO2 with regular pore sizes. By controlling the number of deposition cycles, the TiOx content and filling position in the pore size are controlled to form a TiOx/MIL-101(Cr)-NO2 composite material, which is used to photocatalyze nitrate reduction to produce ammonia.
Low-energy consumption and high-efficiency photocatalytic nitrate reduction are achieved, and the selectivity of nitrate reduction to ammonia reaches 86.4% (ultraviolet light) and 83.7% (visible light), while reducing environmental pollution.
Smart Images

Figure CN119819380A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photocatalytic technology, and in particular to a photocatalytic nitrate reduction ammonia production material TiO x / Preparation method of MIL-101(Cr)-NO2. Background Art
[0002] Photocatalytic reduction of ammonia has received widespread attention as a popular method for synthesizing ammonia. In traditional research, the main method for preparing ammonia is the Haber-Bosch method. However, the reaction conditions of this method are very harsh (20MPa, 400℃), and a large amount of energy is consumed during the synthesis process. Photocatalysis can convert the abundant sunlight in nature into electrical energy or chemical energy, thereby promoting chemical reactions. It has the advantages of being cheap and environmentally friendly, and therefore has attracted much attention. Ammonia is an irreplaceable chemical raw material in human production and life, and it is also the most promising energy transportation carrier. Ammonia is the main component of nitrogen fertilizer, and is also widely used in the manufacture of plastics, pharmaceuticals, explosives, synthetic fibers and resins, as well as industrial chemical products such as printing and dyeing.
[0003] However, most of the world's ammonia supply currently relies on the Haber-Bosch process, which requires high temperatures of 350-550°C and high pressures of 15-25 MPa to drive, releasing up to 300 million tons of CO2 into the atmosphere each year. On the other hand, the accumulation of nitrate (NO3-) in groundwater and surface water caused by fertilizer runoff and industrial wastewater poses a serious threat to the environment and human health, and chemical (electrodialysis, ion exchange, etc.) and biological (denitrification) methods involve large amounts of wastewater and energy consumption. Therefore, there is an urgent need to develop a low-energy, efficient and easy-to-implement photocatalytic nitrate reduction ammonia material TiO x / Preparation method of MIL-101(Cr)-NO2. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a photocatalytic nitrate reduction ammonia production material TiO x / MIL-101(Cr)-NO2 preparation method, with the advantages of low energy consumption, high efficiency and easy implementation, solves the problem that most of the world's ammonia supply currently relies on the Haber-Bosch process, which requires high temperature of 350-550℃ and high pressure of 15-25MPa to drive, releasing up to 300 million tons of CO2 into the atmosphere every year. On the other hand, the accumulation of nitrate (NO3-) in groundwater and surface water caused by fertilizer runoff and industrial wastewater poses a serious threat to the environment and human health, and chemical (electrodialysis, ion exchange, etc.) and biological (denitrification) methods involve large amounts of wastewater and energy consumption.
[0005] To achieve the above object, the present invention provides the following technical solution: a photocatalytic nitrate reduction ammonia production material TiO x / The preparation method of MIL-101(Cr)-NO2 comprises the following steps:
[0006] Step 1: Synthesis of MIL-101(Cr)
[0007] S1. Dissolve 332-365 mg of terephthalic acid and 800-900 mg of Cr(NO3)3·9H2O in 14-18 mL of deionized water by ultrasonic treatment.
[0008] S2, adding 0.1-0.3 mL of HF and stirring it evenly to obtain a mixed solution A;
[0009] S3, then transfer the mixed solution A to a polytetrafluoroethylene-lined reactor with a capacity of 50 mL;
[0010] S4, then allowing the mixed solution A to react at a temperature of 220-236°C for 8 hours, and after the reaction is completed, naturally cooling to room temperature;
[0011] S5, washing with N,N-dimethylformamide, water and ethanol three times respectively, and collecting by centrifugation at a speed of 8000-8800 r / min to obtain product A;
[0012] S6. Finally, the product A is placed in a vacuum environment at 60-65° C. and dried for 12-16 hours to obtain MIL-101 (Cr);
[0013] Step 2: Synthesis of MIL-101(Cr)-NO2
[0014] S1. Add 100-120 mg of ML-101(Cr) to a mixture of 7-11 mL of concentrated H2SO4 and 5-8 mL of concentrated HNO3;
[0015] S2, then stirring at 0-2°C for 6 hours to obtain a mixture A;
[0016] S3, pour 50-60 mL of ice water into the mixture A while stirring, and warm it to room temperature;
[0017] S4, then washing the mixture A with water and ethanol three times respectively, and then centrifuging and collecting at a speed of 8000-8800 r / min to obtain a green crystalline product A;
[0018] S5. Finally, the green crystal product A is placed in a vacuum environment at 60-65° C. and dried for 12-14 hours to obtain MIL-101(Cr)-NO2;
[0019] Step 3: Synthesis of TiO x / MIL-101(Cr)-NO2
[0020] Take 15-20 mg of MIL-101(Cr)-NO2 and put it into the sample tray. Place the sample tray on the sample platform of the ALD system, set the deposition conditions and start the deposition program to deposit TiO in the pore structure of MOF. x At the same time, the process cycle is adjusted to control the deposition amount. After the deposition process is completed, TiO x / MIL-101(Cr)-NO2.
[0021] Preferably, the mass ratio of terephthalic acid to Cr(NO3)3·9H2O is 1:3.5.
[0022] Furthermore, the method of ultrasonic treatment of phthalic acid and Cr(NO3)3·9H2O is as follows:
[0023] S1, take phthalic acid, Cr(NO3)3·9H2O and water and put them into ultrasonic dissolver;
[0024] S2. Set the frequency of the ultrasonic dissolver to 20-40KHz, the power to 5-20W / L, the temperature to 20-30℃, and the dissolution time to 3-5min;
[0025] S3. After fully dissolved, pour the solution into the stirring equipment.
[0026] Preferably, the mass percentage (wt) of HF used is 20-40%, and the amounts of N,N-dimethylformamide, water and ethanol used in the washing process are 100 ml, 150 ml and 80 ml respectively.
[0027] Preferably, the product A is placed in a vacuum dryer for drying, and the mass ratio of ML-101 (Cr), concentrated H2SO4 and HNO3 is 20:1:0.95.
[0028] Preferably, the mixture A is added with ice water and then heated to 20-40° C. by a heating device.
[0029] Furthermore, when the mixture A is washed with water and ethanol, the amounts used for the first washing are 120 ml and 80 ml respectively, the amounts used for the second washing are 100 ml and 75 ml respectively, and the amounts used for the third washing are 95 ml and 65 ml respectively. After washing, a centrifugal separator is used for centrifugal collection.
[0030] Furthermore, the deposited TiO x Process cycles include 10, 20, 30, 40 and 50 layers of TiO x , denoted as TiOx / MOF: TiO x -10 / MOF, TiO x -20 / MOF, TiO x -30 / MOF, TiO x -40 / MOF, TiO x -50 / MOF, wherein MOF represents MIL-101(Cr)-NO2.
[0031] Preferably, the deposition conditions include:
[0032] The precursor of the Ti element is tetrakis(dimethylamino)titanium(IV) with a purity of 99.99%, while the source of the O element is water molecules;
[0033] The sample platform temperature is 150°C, the heating pipeline temperature is 450°C, and the pipeline temperature for conveying liquid is 120°C;
[0034] One deposition cycle consisted of a tetrakis(dimethylamino)titanium(IV) pulse of 0.2 s, a N2 purge of 40 s, a H2O pulse of 0.0151 s, and a N2 purge of 40 s;
[0035] The TiO x / After the synthesis of MIL-101(Cr)-NO2, surface characteristics analysis, photoelectric performance analysis, photocatalytic analysis and mechanism analysis were carried out
[0036] Compared with the prior art, the technical solution of this application has the following beneficial effects:
[0037] 1. The present invention uses atomic layer deposition technology to confine TiO in MIL-101(Cr)-NO2 with regular apertures. x The number of deposition cycles can be used to control the filling position and TiO x content, ensuring the uniqueness of the molecular compartment structure within the confinement of MIL-101(Cr)-NO2, and the TiO x The synergistic effect between the units and the catalytic metal clusters in the MIL-101(Cr)-NO2 framework can promote the absorption of light and enhance the photocatalytic performance.
[0038] 2. TiO x When the molecular clusters grow in situ in the MOF cavity, the composite material can maintain charge conservation, and the trivalent chromium in MIL-101(Cr)-NO2 is transformed into divalent chromium, which increases the active sites of the composite material and improves the catalytic performance of the catalyst.
[0039] 3. The present invention uses atomic layer deposition technology to in-situ grow TiO in the MOF cavity x , to prepare TiOx / MI L-101(Cr)-NO2 composite photocatalytic material, under ultraviolet light (100mW / cm2) irradiation, the NH4+ generation rate is 64.11mmol / gcat. / h, and the selectivity of nitrate reduction to ammonia reaches 86.4%; under visible light (>400nm, 100mW / cm2) irradiation, the NH4+ generation rate is 35.79mmol / gcat. / h, and the selectivity of nitrate reduction to ammonia reaches 83.7%. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 TEM and SEM images of MOF of the present invention and TiO x TEM and SEM images of -30 / MOF;
[0041] Figure 2 The TiO x -EDS image of 30 / MOF and its element distribution;
[0042] Figure 3 is the pore size distribution histogram of the present invention;
[0043] Figure 4 This is a series of TiO x / N2 adsorption-desorption isotherm of MOF;
[0044] Figure 5 a) MOF and TiO x / MOF's 1.6-12° small angle X RD image; (b) TiO x -30 / MOF high resolution image;
[0045] Figure 6 The MOF and TiO x / MOF: (a) UV-Vis spectrum, (b) band gap diagram, (c) valence band diagram and (d) band structure diagram;
[0046] Figure 7 Graphs of (a) photocatalytic nitrate reduction performance and (c) stability and (b) photocatalytic nitrate reduction selectivity and (d) stability of the present invention;
[0047] Figure 8 a) MOF and TiO x / MOF small angle of 1.6-12° and (b) TiO x -30 / MOF X RD diagram. DETAILED DESCRIPTION
[0048] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] Embodiment 1
[0050] In this embodiment, a photocatalytic nitrate reduction ammonia production material TiO x / The preparation method of MIL-101(Cr)-NO2 comprises the following steps:
[0051] Step 1: Synthesis of MIL-101(Cr)
[0052] S1. 332 mg of terephthalic acid and 800 mg of Cr(NO3)3·9H2O were completely dissolved in 14 mL of deionized water by ultrasonic treatment;
[0053] S2, adding 0.1 mL of HF and stirring it evenly to obtain a mixed solution A;
[0054] S3, then transfer the mixed solution A to a polytetrafluoroethylene-lined reactor with a capacity of 50 mL;
[0055] S4, then allowing the mixed solution A to react at a temperature of 220° C. for 8 hours, and after the reaction is completed, naturally cooling to room temperature;
[0056] S5, washing with N,N-dimethylformamide, water and ethanol three times respectively, and collecting by centrifugation at a centrifuge speed of 8000 r / min to obtain product A;
[0057] S6. Finally, the product A was dried at 60° C. in a vacuum environment for 12 hours to obtain MIL-101 (Cr);
[0058] Step 2: Synthesis of MIL-101(Cr)-NO2
[0059] S1. Add 100 mg of ML-101(Cr) to a mixture of 7 mL of concentrated H2SO4 and 5 mL of concentrated HNO3;
[0060] S2, then stirring at 0°C for 6 hours to obtain a mixture A;
[0061] S3, pour 50 mL of ice water into the mixture A while stirring, and warm it to room temperature;
[0062] S4, then washing the mixture A with water and ethanol three times respectively, and then centrifuging at a speed of 8000 r / min to obtain a green crystalline product A;
[0063] S5. Finally, the green crystalline product A was placed in a vacuum environment at 60° C. and dried for 12 hours to obtain MIL-101(Cr)-NO2;
[0064] Step 3: Synthesis of TiO x / MIL-101(Cr)-NO2
[0065] Take 15 mg of MIL-101(Cr)-NO2 and put it into the sample tray. Place the sample tray on the sample platform of the ALD system, set the deposition conditions and start the deposition program to deposit TiO in the pore structure of MOF. x At the same time, the process cycle is adjusted to control the deposition amount. After the deposition process is completed, TiO x / MIL-101(Cr)-NO2.
[0066] Embodiment 2
[0067] In this embodiment, a photocatalytic nitrate reduction ammonia production material TiO x / The preparation method of MIL-101(Cr)-NO2 comprises the following steps:
[0068] Step 1: Synthesis of MIL-101(Cr)
[0069] S1. 365 mg of terephthalic acid and 900 mg of Cr(NO3)3·9H2O were completely dissolved in 18 mL of deionized water by ultrasonic treatment;
[0070] S2, adding 0.3 mL of HF and stirring it evenly to obtain a mixed solution A;
[0071] S3, then transfer the mixed solution A to a polytetrafluoroethylene-lined reactor with a capacity of 50 mL;
[0072] S4, then allowing the mixed solution A to react at a temperature of 236° C. for 8 hours, and after the reaction is completed, naturally cooling to room temperature;
[0073] S5, washing with N,N-dimethylformamide, water and ethanol three times respectively, and collecting by centrifugation at a centrifuge speed of 8800 r / min to obtain product A;
[0074] S6. Finally, the product A was dried at 65° C. in a vacuum environment for 16 hours to obtain MIL-101 (Cr);
[0075] Step 2: Synthesis of MIL-101(Cr)-NO2
[0076] S1. Add 120 mg of ML-101 (Cr) to a mixture of 11 mL of concentrated H2SO4 and 8 mL of concentrated HNO3;
[0077] S2, then stirring at 2°C for 6 hours to obtain a mixture A;
[0078] S3, pour 60 mL of ice water into mixture A while stirring, and warm it to room temperature;
[0079] S4, then washing the mixture A with water and ethanol three times respectively, and then centrifuging at a speed of 8800 r / min to obtain a green crystalline product A;
[0080] S5. Finally, the green crystalline product A was placed in a vacuum environment at 65°C and dried for 14 hours to obtain MIL-101(Cr)-NO2;
[0081] Step 3: Synthesis of TiO x / MIL-101(Cr)-NO2
[0082] Take 20 mg of MIL-101(Cr)-NO2 and put it into the sample tray. Place the sample tray on the sample platform of the ALD system, set the deposition conditions and start the deposition program to deposit TiO in the pore structure of MOF. x At the same time, the process cycle is adjusted to control the deposition amount. After the deposition process is completed, TiO x / MIL-101(Cr)-NO2.
[0083] Specifically, the TiO x Process cycles include 10, 20, 30, 40 and 50 layers of TiO x , denoted as TiO x / MO F: TiO x -10 / MOF, TiO x -20 / MOF, TiO x -30 / MOF, TiO x -40 / MOF, TiO x -50 / MOF, MOF stands for MIL-101(Cr)-NO 2, .
[0084] In the above embodiment, the deposition conditions include:
[0085] The precursor of the Ti element is tetrakis(dimethylamino)titanium(IV) with a purity of 99.99%, while the source of the O element is water molecules;
[0086] The sample platform temperature is 150°C, the heating pipeline temperature is 450°C, and the pipeline temperature for conveying liquid is 120°C;
[0087] One deposition cycle consisted of a tetrakis(dimethylamino)titanium(IV) pulse of 0.2 s, a N2 purge of 40 s, a H2O pulse of 0.0151 s, and a N2 purge of 40 s.
[0088] By adopting the above technical scheme, the synthesized TiO x / The surface characteristics analysis of MIL-101(Cr)-NO2 is as follows:
[0089] See also Figure 1 In order to understand the morphology of the material, transmission electron microscopy (TEM) and scanning electron microscopy (SEM) tests were first performed. Figures a and c are TEM and SEM images of MOF, respectively. From the image analysis, most of the MOFs prepared in this work present an octahedral structure with a size of 400nm. In this work, atomic layer deposition technology was used to deposit MOF materials for 30 cycles, and then TEM and SEM tests were performed on the composite materials. From the test results, the TiO prepared in this work x -30 / MOF, (b, d in the figure still maintain the octahedral structure, and the size has not changed significantly, proving that the material structure has not changed after 30 cycles of deposition. At the same time, TiO x -30 / MOF has a smooth surface, indicating that TiO x It was not deposited on the MOF surface.
[0090] See also Figure 2 In order to more clearly understand the structure and composition of the catalyst, the material was subjected to energy spectroscopy. X EDS analysis can analyze the element distribution and content in the prepared material. The figure shows the uniform distribution of elements C, O, Cr, N and Ti on the sample. In the element distribution, it is found that the imaging area of Ti element is smaller than that of C element, which confirms the TiO x The molecules cluster within the MOF cavities, rather than on the surface of the material.
[0091] See also Figure 3 , the fitting results of the isotherms using the DFT model reveal the pore size distribution in each sample. In the figure, there are three types of pore sizes in MOF: micropores (1.6-2nm), mesopores 1 (2-3nm) and mesopores 2 (3-4nm). In the initial stage, the proportion of space occupied by mesopores 1 (approximately 2-3nm) decreased significantly, while the proportion of mesopores 2 (3-4nm) decreased relatively moderately. After 30 deposition cycles, mesopores 1 (2-3nm) were almost completely filled, while the proportion of space occupied by micropores (1.6-2nm) showed a gradual increase.
[0092] See also Figure 4 By using N2 adsorption-desorption isotherms to analyze the BET surface area porosity of the composite structure, it can be observed from the figure that the composite material x As the deposition cycle number increases, the BET specific surface area and pore volume decrease, indicating that the pores of the material are gradually filled with TiO x Filling. At P / P0=0.2, there is an upward step in the gas absorption rate, where P and P0 represent the gas pressure and saturation pressure respectively, which proves that TiO x All pore structures of MOF are mesoporous. However, as the number of deposition cycles continues to increase, the position of this platform moves down to a lower level, reflecting that the interior of MOF is gradually being filled up, such as TiO x / BET specific surface area and pore volume table of MIL-101(Cr).
[0093]
[0094] See also Figure 5 In order to understand the microstructure of the material more clearly, high-resolution testing was performed. The pore distribution in the MOF can be seen in the image. However, in the TiO x After the molecular clusters are deposited, the pores of MOF become blurred. This is because the TiO x After the molecular clusters grow in situ in the MOF cavity, the crystallinity of MOF is damaged to a certain extent. At the same time, TiO x The existence of molecular clusters found that TiO x The molecular clusters exist in the pores of MOF, which confirms that TiO x The molecular clusters are deposited into the cavities of the MOF.
[0095] See also Figure 6 The samples were tested by UV-vis. The MOF and its TiO x The UV-Vis curve of / MOF shows that all the prepared materials have obvious absorption peaks at 200-400nm and another absorption peak at about 600nm. These two absorption peaks correspond to the π-π* conversion process and the dd spin-allowed transition of Cr3+ ions. x After precipitation in MOF, the overall light absorption performance is greatly improved. This change in light absorption performance is attributed to TiO xThe bandgap width is obtained by calculating the absorption spectrum through the Tauc-Plot method. x The band gaps of TiO-30 / MOF samples are 3.06eV and 1.91eV respectively. x Deposition in MOF pores can significantly narrow the band gap of the system and enhance the light response.
[0096] The data in Figure c show that MOF and TiO x The valence band position of the molecular cluster X PS valence band spectrum analysis, the authors obtained their values of 1.56eV and 2.89eV respectively. Further, Figure d draws a band structure diagram, after atomic layer deposition technology, TiO x The conduction band position of the molecular cluster is about -0.41eV, while the conduction band position of MOF is close to -1.50eV.
[0097] See also Figure 7 , TiO x The -30 / MOF sample has the best photocatalytic properties. Under ultraviolet light (100mW / cm2), the NH4+ generation rate is 64.11mmol / gcat. / h, and the selectivity of nitrate reduction to ammonia is 86.4%; under visible light (>400nm, 100mW / cm2), the NH4+ generation rate is 35.79mmol / gcat. / h, and the selectivity of nitrate reduction to ammonia is 83.7%. TiO x The in situ growth of molecular clusters is inhibited by the molecular compartments formed by MOF pores, shortening the TiO x The photoelectron transfer pathway to the MOF facilitates charge separation and transfer and drives the reaction of nitrate on the catalyst surface.
[0098] See also Figure 8 , the nitrate adsorption experiment of the material was carried out: 10 mL of 1 mmol / L potassium nitrate solution was added to two 20 mL glass bottles respectively, and then 1 mg of MOF and TiO were added respectively. x -30 / MOF, and then let it stand for 4 hours. The amount of nitrate reduction was calculated by spectrophotometry, and the results are shown in the figure. From this, we can draw the following conclusions: after 30 layers of TiO x After the molecular cluster, the adsorption amount of nitrate is 8.9 times that before deposition. This is because TiO x There are oxygen vacancies in the molecular clusters, which can effectively regulate the electronic structure of the catalyst surface, thereby promoting the adsorption of nitrate ions.
[0099] In summary, the present invention uses atomic layer deposition technology to in-situ grow TiO in the MOF cavity.x , to prepare TiO x / MOF composite photocatalytic material. Under ultraviolet light (100mW / cm2), the NH4+ generation rate is 64.11mmol / gcat. / h, and the selectivity of nitrate reduction to ammonia reaches 86.4%; under visible light (>400nm, 100mW / cm2), the NH4+ generation rate is 35.79mmol / gcat. / h, and the selectivity of nitrate reduction to ammonia reaches 83.7%. The porous structure of MOF enriches nitrate ions, which increases the concentration of reactants and reduces the Gibbs free energy, thereby improving the catalytic performance of the material. At the same time, the TiO x The synergistic effect between the motifs and catalyst clusters can effectively improve the utilization of the visible light spectrum and the photocatalytic activity.
[0100] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0101] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A photocatalytic nitrate reduction ammonia production material TiO x / The preparation method of MIL-101(Cr)-NO2 is characterized in that: The steps include: Step 1: Synthesis of MIL-101(Cr) S1. Dissolve 332-365 mg of terephthalic acid and 800-900 mg of Cr(NO3)3·9H2O in 14-18 mL of deionized water by ultrasonic treatment. S2, adding 0.1-0.3 mL of HF and stirring it evenly to obtain a mixed solution A; S3, then transfer the mixed solution A to a polytetrafluoroethylene-lined reactor with a capacity of 50 mL; S4, then allowing the mixed solution A to react at a temperature of 220-236°C for 8 hours, and after the reaction is completed, naturally cooling to room temperature; S5, washing with N,N-dimethylformamide, water and ethanol three times respectively, and collecting by centrifugation at a speed of 8000-8800 r / min to obtain product A; S6. Finally, the product A is placed in a vacuum environment at 60-65° C. and dried for 12-16 hours to obtain MIL-101 (Cr); Step 2: Synthesis of MIL-101(Cr)-NO2 S1. Add 100-120 mg of ML-101(Cr) to a mixture of 7-11 mL of concentrated H2SO4 and 5-8 mL of concentrated HNO3; S2, then stirring at 0-2°C for 6 hours to obtain a mixture A; S3, pour 50-60 mL of ice water into the mixture A while stirring, and warm it to room temperature; S4, then washing the mixture A with water and ethanol three times respectively, and then centrifuging and collecting at a speed of 8000-8800 r / min to obtain a green crystalline product A; S5. Finally, the green crystal product A is placed in a vacuum environment at 60-65° C. and dried for 12-14 hours to obtain MIL-101(Cr)-NO2; Step 3: Synthesis of TiO x / MIL-101(Cr)-NO2 Take 15-20 mg of MIL-101(Cr)-NO2 and put it into the sample tray. Place the sample tray on the sample platform of the ALD system, set the deposition conditions and start the deposition program to deposit TiO in the pore structure of MOF. x At the same time, the process cycle is adjusted to control the deposition amount. After the deposition process is completed, TiO x / MIL-101(Cr)-NO2.
2. A photocatalytic nitrate reduction ammonia production material TiO according to claim 1 x / The preparation method of MIL-101(Cr)-NO2 is characterized in that: The mass ratio of terephthalic acid to Cr(NO3)3·9H2O is 1:3.
5.
3. A photocatalytic nitrate reduction ammonia production material TiO according to claim 1 x / The preparation method of MIL-101(Cr)-NO2 is characterized in that: The method of ultrasonic treatment of phthalic acid and Cr(NO3)3·9H2O is as follows: S1, take phthalic acid, Cr(NO3)3·9H2O and water and put them into ultrasonic dissolver; S2. Set the frequency of the ultrasonic dissolver to 20-40KHz, the power to 5-20W / L, the temperature to 20-30℃, and the dissolution time to 3-5min; S3. After fully dissolved, pour the solution into the stirring equipment.
4. A photocatalytic nitrate reduction ammonia production material TiO according to claim 1 x / The preparation method of MIL-101(Cr)-NO2 is characterized in that: The mass percentage (wt) of HF used is 20-40%, and the amounts of N,N-dimethylformamide, water and ethanol used in the washing process are 100 ml, 150 ml and 80 ml respectively.
5. The photocatalytic nitrate reduction ammonia production material TiO according to claim 1 x / The preparation method of MIL-101(Cr)-NO2 is characterized in that: The product A is placed in a vacuum dryer for drying, and the mass ratio of ML-101 (Cr), concentrated H2SO4 and HNO3 is 20:1:0.
95.
6. The photocatalytic nitrate reduction ammonia production material TiO according to claim 1 x / The preparation method of MIL-101(Cr)-NO2 is characterized in that: After adding ice water, the mixture A is heated to 20-40° C. by a heating device.
7. The photocatalytic nitrate reduction ammonia production material TiO according to claim 1 x / The preparation method of MIL-101(Cr)-NO2 is characterized in that: When the mixture A is washed with water and ethanol, the amounts used for the first washing are 120 ml and 80 ml respectively, the amounts used for the second washing are 100 ml and 75 ml respectively, and the amounts used for the third washing are 95 ml and 65 ml respectively. After washing, centrifugal collection is performed using a centrifugal separator.
8. The photocatalytic nitrate reduction ammonia production material TiO according to claim 1 x / The preparation method of MIL-101(Cr)-NO2 is characterized in that: The deposited TiO x Process cycles include 10, 20, 30, 40 and 50 layers of TiO x , denoted as TiO x / MOF: TiO x -10 / MOF, TiO x -20 / MOF, TiO x -30 / MOF, TiO x -40 / MOF, TiO x -50 / MOF, wherein MOF represents MIL-101(Cr)-NO2.
9. The photocatalytic nitrate reduction ammonia production material TiO according to claim 1 x / The preparation method of MIL-101(Cr)-NO2 is characterized in that: The deposition conditions include: the precursor of the Ti element is tetrakis(dimethylamino)titanium(IV) with a purity of 99.99%, and the source of the O element is water molecules; The sample platform temperature is 150°C, the heating pipeline temperature is 450°C, and the pipeline temperature for conveying liquid is 120°C; One deposition cycle consisted of a tetrakis(dimethylamino)titanium(IV) pulse of 0.2 s, a N2 purge of 40 s, a H2O pulse of 0.0151 s, and a N2 purge of 40 s. The TiO x After the synthesis of / MIL-101(Cr)-NO2, surface characteristics analysis, photoelectric performance analysis, photocatalytic analysis and mechanism analysis were carried out.